Gut microbiota and plasma metabolites in pregnant mothers and infant atopic dermatitis: A multi-omics studyKey Message - Bingqian Du, MA.Sc; Aga Shama, BA.Sc; Yi Zhang, BA.Sc; Baolan Chen, MA.Sc; Yongqi Bu, BA.Sc; Pei-an Chen, MA.Sc; Chuzhi Lin, BA.Sc; Jie Liu, MA.Sc; Juan Zheng, MA.Sc; Zhenjun Li, MD, PhD; Qingsong Chen, PhD; Yu Sun, PhD; et al. (World Allergy Organization Journal)
Background: Many studies reported the influence of infants' gut microbiota on atopic dermatitis (AD) postnatally, yet the role of maternal gut microbiota and plasma metabolites in infants’ AD remains largely unexplored. Methods: Sixty-three pregnant mother-infants were enrolled and followed after childbirth in Guangzhou, China. Demographic information, maternal stool and plasma samples, and records for infants’ AD were collected. Maternal gut microbiota/metabolome and plasma metabolome were profiled using shotgun metagenomics and non-targeted metabolomics. Logistic regression and multi-omics analysis were used to explore characteristic maternal gut microbiota in the AD and health groups. Results: The α-diversity of maternal gut microbiota in health group was significantly higher than AD group (Shannon diversity P = 0.02, Simpson diversity P = 0.04). Short-chain fatty acids (SCFAs) producing microorganisms, including Faecalibacterium, Roseburia, Butyricicoccus, and Ruminococcus, as well as the abundance of phenylalanine, tyrosine, and tryptophan biosynthesis pathway, were enriched in health group (LDA>2 and P < 0.05). Virulent factors (VFs) involved in immune modulation were enriched in the health group, while VFs involving in adhesin were enriched in the AD group (P < 0.05). Metabolomic analysis showed that a polyunsaturated fatty acid/linoleic acid, 13S-hydroxyoctadecadienoic, were negatively associated with AD in both the gut and plasma samples (FDR<0.05). Several other linoleic acids and flavonoids were negatively associated with AD (FDR<0.05). Neural network analysis revealed that microorganisms enriched in health group may produce these protective fatty acids. Conclusions: Our findings show that maternal gut microorganisms/metabolites and plasma metabolites during pregnancy impact subsequent pathogenesis of infants AD. This illuminates new strategies against early AD in offspring.